Selenium Donor Inhibited Hepatitis B Virus Associated Hepatotoxicity via the Apoptosis and Ferroptosis Pathways - Jingdong Shi; Zhen Liu; Weina Li; Di Wang (Analytical Cellular Pathology)
Background and Aim. Selenium possesses anticancer and antiviral properties, but its mechanism of action remains unclear. Especially, the impact of selenium on hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) remains unknown. This study aimed to investigate the inhibitory properties of selenium on HBV replication and its related hepatotoxicity via the apoptosis and ferroptosis pathways. Methods. The serum selenium level was determined in 45 patients with HBV-positive HCC (HBV+-HCC group), 45 patients with chronic hepatitis B virus infection (CHB group), and 45 healthy cases (HC group). The sodium selenite (Na2SeO3)-treated HepG2.2.15 cells were used to observe the regulatory role of selenium on HBV replication. D-GalN/erastin-added HL7702 was used to determine the regulatory roles of Na2SeO3 on hepatotoxicity or hepatocyte ferroptosis. The wild-type (WT) C57BL/6 mice and HBx-Tg mice were received lipopolysaccharide (LPS)/D-GalN, together with or without Na2SeO3 administration for indicated period. Following euthanasia, the blood and liver tissue samples were collected, and specific markers were evaluated subsequently. Results. The serum selenium level was downregulated in patients with HBV-positive HCC (HBV+-HCC group) (57.2 ± 22.5 μg/L vs. 91.8 ± 43.9 μg/L, P<0.001), and its higher level could provide a better prognosis in these patients. The treatment using Na2SeO3, a selenium donor, at high concentration (5 μM), suppressed the HBV replication by about 50% in HepG2.2.15 cells (P<0.001), through promoting apoptotic cell death and inhibiting cellular inhibitor of apoptosis proteins (cIAPs). In addition, low-dose (500 nM) Na2SeO3 could almost totally reversed the hepatotoxicity induced by hepatitis B virus X protein (HBx) (P<0.001), which were the main causes of HCC in patients. Studies at the cellular levels showed that low-dose Na2SeO3 inhibited the HBx-related hepatotoxicity by blocking ferroptosis, and glutathione peroxidase 4 (GPX4) mediated this regulatory role. Mice model results confirmed that the treatment with Na2SeO3 could mitigated LPS/D-GalN-induced hepatic injury through ferroptosis pathways. Conclusion. Selenium regulated the dual cell death in different HCC stages via different signaling pathways, which could partly explain the anti-HBV and anti-HCC properties of selenium.